KKN dengan Mode Hybrid di Wilayah Kavling Rawa Bunga, Tangerang Selatan - Fathan Mubina Dewadi; Lutfi Yudi Kiswanto; Adhifa Mizan Ghifary (Journal of Entrepreneurship and Community Innovations, 2022)
Higher education has three important things known as Tri Darma, namely education and teaching, research and community service. In this activity, the focus is on community service with cross-departmental collaboration with Budi Lihur University in collaboration with several local environmental volunteers. The work program planned by Budi Luhur University students related to Community Service Program includes 3 types of activities, namely a webinar socializing healthy living, a torch relay in commemorating the Birthday of the Prophet Muhammad and aquaponic cultivation methods. The output of the achievement of this real  work course is for the community to receive the latest education with the millennial concept, namely adequate knowledge in dealing with COVID-19, while for students, namely to get direct experience of observations of what they learn during lectures.